Sustainable Education Using Augmented Reality in Vocational Certification Courses - Lee, Chia-Jung; Hsu, Yen (Sustainability, 2021)
In the field of vocational education, no studies have examined the use of augmented reality (AR) learning technologies in the teaching of cosmetology. However, this study proposed the “Makeup AR” learning approach and conducted a quasi-experiment to examine the interaction effect between said approach and students with active and reflective learning styles. The research participants were 70 students from a vocational senior high school. The experimental group comprised 36 participants who were taught using Makeup AR, and the control group comprised 34 participants who were taught using an e-book. The results revealed that the use of Makeup AR improved students’ learning effectiveness. The proposed approach also effectively enhanced students’ self-efficacy and reduced their cognitive load. The students with a reflective learning style had a higher cognitive load than those with an active learning style when using the e-book learning approach. No difference in learning motivation was noted between the experimental and control groups. Overall, Makeup AR is suitable for makeup design certification courses in vocational senior high schools and can enhance learning effectiveness, improve students’ self-efficacy, and reduce cognitive load. This study suggests that the implementation of AR technology in certification courses can be beneficial to learning outcomes.